2018
DOI: 10.1039/c8cc00328a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and evaluation of new acridone derivatives for selective binding of oncogene c-myc promoter i-motifs in gene transcriptional regulation

Abstract: We synthesized a series of acridone derivatives for specific binding ligands of i-motifs. Subsequent evaluations showed that B19 could selectively bind to and stabilize the c-myc promoter i-motif without significant binding to the G-quadruplex and duplex DNA. This caused down-regulation of c-myc transcription and expression, resulting in tumor cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Recently, PBP1 and acridone derivatives have been developed as i‐motif binders, and shown to regulate the transcriptional activities of bcl‐2 and c‐myc genes, respectively. However, despite the growing number of reports on i‐motif‐interacting agents, so far, there is little structural information available on complexes between ligands and the i‐motif …”
Section: Methodsmentioning
confidence: 99%
“…Recently, PBP1 and acridone derivatives have been developed as i‐motif binders, and shown to regulate the transcriptional activities of bcl‐2 and c‐myc genes, respectively. However, despite the growing number of reports on i‐motif‐interacting agents, so far, there is little structural information available on complexes between ligands and the i‐motif …”
Section: Methodsmentioning
confidence: 99%
“…Recently, Shu et al. developed a series of acridone derivatives and determined that one of these derivatives, B19, is capable of binding to and stabilizing the i-motif formed in the c-MYC promoter resulting in downregulation of gene expression and eventually to tumor cell death ( 89 ). The characterization of more i-motif structures at high resolution as well as its stabilization at neutral pH will contribute to increase the number of ligands that stabilize i-motifs.…”
Section: Biological Relevance Of I-motif Structuresmentioning
confidence: 99%
“…Recently, it has been further demonstrated that i-motif structures can form in promoters and telomeric regions by using i-motif specific antibodies ( 19 ). We have also revealed that an acridone derivative could selectively bind to oncogene C-MYC promoter i-motif and down-regulate gene transcription and translation ( 26 ).…”
Section: Introductionmentioning
confidence: 99%